2013
DOI: 10.1371/journal.pone.0071990
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Epstein–Barr Virus DNA in Deeper Periodontal Pockets of Chronic Periodontitis in Japanese Patients

Abstract: Periodontitis, a complex chronic inflammatory disease caused by subgingival infection, is among the most prevalent microbial diseases in humans. Although traditional microbiological research on periodontitis has focused on putative bacteria such as Porphyromonas gingivalis, the herpes virus is proposed to be involved in the pathogenesis of periodontitis because bacterial etiology alone does not adequately explain various clinical aspects. In this study, we established for the first time, more Epstein–Barr viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 34 publications
4
126
2
2
Order By: Relevance
“…We previously reported that Epstein-Barr virus (EBV) DNA was detected more frequently in deeper (≥5 mm) PPD sites of CP patients than in shallow (≤3 mm) PPD sites or in healthy controls (4). In addition, coexistence of EBV and Porphyromonas gingivalis was significantly more frequent in deep PPD sites of patients as compared with shallow PPD sites and healthy controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously reported that Epstein-Barr virus (EBV) DNA was detected more frequently in deeper (≥5 mm) PPD sites of CP patients than in shallow (≤3 mm) PPD sites or in healthy controls (4). In addition, coexistence of EBV and Porphyromonas gingivalis was significantly more frequent in deep PPD sites of patients as compared with shallow PPD sites and healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…Periodontopathic bacteria increase the risk of periodontitis, and immune responses against bacterial products and subsequent secretion of proinflammatory cytokines are crucial in periodontal tissue destruction (4,5). Interleukin-1β (IL-1β) is an important mediator of inflammatory response and is involved in cell proliferation, differentiation, and apoptosis, and in the pathophysiology of periodontitis (6).…”
Section: Introductionmentioning
confidence: 99%
“…It affects the periodontal tissues, and when advanced can result in tissue destruction, occasional pain, alveolar bone resorption, and eventual tooth loss (1)(2)(3). The response to periodontal pathogens is determined by the nature and control of both adaptive and innate immune responses (4).…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by specific bacteria and viruses and results in progressive destruction of the periodontal ligament and alveolar bone, with pocket formation (1,2). The rate of disease progression may be increased by local, systemic, and environmental factors that influence normal host-bacteria interaction.…”
Section: Introductionmentioning
confidence: 99%